2020
DOI: 10.1177/1533033820973277
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of DDR1 Promotes Migration, Invasion, Though EMT-Related Molecule Expression and COL4A1/DDR1/MMP-2 Signaling Axis

Abstract: Purpose: Discoidin domain receptor 1 (DDR1) belongs to a novel class of receptor tyrosine kinases. Previous evidence indicates that DDR1 overexpression promotes the aggressive growth of bladder cancer (BC) cells. This study aimed to investigate the molecular mechanisms by which DDR1 influences BC. Methods: DDR1 was transfected into human BC RT4 cells. DDR1, COL4A1, and MMP-2 expression in 30 BC tissues and paired adjacent tissues were examined by real-time polymerase chain reaction (RT-PCR) and immunohistochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…Moreover, we demonstrated that DDR1 promotes thyroid cancer cell dedifferentiation and the acquisition of a stemlike phenotype by enhancing the IGF-2/IR-A autocrine signaling loop [9,10] and plays a critical role in promoting bladder cancer cell motility by linking the IGF1R and IR-A to the regulation of F-actin cytoskeleton dynamics [15]. Collectively, these data uncover novel, non-canonical DDR1 functions, which strongly support the pro-tumorigenic and pro-metastatic role of DDR1 [16][17][18].…”
Section: Introductionsupporting
confidence: 60%
“…Moreover, we demonstrated that DDR1 promotes thyroid cancer cell dedifferentiation and the acquisition of a stemlike phenotype by enhancing the IGF-2/IR-A autocrine signaling loop [9,10] and plays a critical role in promoting bladder cancer cell motility by linking the IGF1R and IR-A to the regulation of F-actin cytoskeleton dynamics [15]. Collectively, these data uncover novel, non-canonical DDR1 functions, which strongly support the pro-tumorigenic and pro-metastatic role of DDR1 [16][17][18].…”
Section: Introductionsupporting
confidence: 60%
“…EMT plays a vital role in tumour invasion and progression, including tumour initiation, malignant progression, tumour cell migration, metastasis, and treatment resistance of tumours 42 . During EMT, the polarized epithelial cells lose their tight intercellular junctions to gradually differentiate into cells with mesenchymal properties, allowing rapid cell migration and large collagen formation 43,44 . DDR1 participates in many cancers, including prostate cancer, 45 liver cancer, 46 gastric cancer, 47 kidney cancer, 48 osteosarcoma, 49 and colorectal cancer 50 .…”
Section: Resultsmentioning
confidence: 99%
“…DDR1 mediates the EMT process, tumour invasion, and metastasis. DDR1 can participate in the EMT through the following mechanism 44,51,53,54 DDR1 regulates EMT through cadherin switching The switching of epithelial phenotype E‐cadherin into mesenchymal phenotypes, such as N‐cadherin and vimentin, is a characteristic of EMT 55,56 .…”
Section: Resultsmentioning
confidence: 99%
“…Ambrogio et al reported that DDR1 could be a therapeutic target for KRAS-driven non-small-cell lung cancer [ 44 ]. Another primary study revealed that in bladder cancer upregulation of DDR1 could promote invasion and migration via the EMT pathway [ 45 ]. Considering the above research results which can be used as the verification of our bioinformatics results, it may indicate that COL3A1 may act as a molecular biomarker mediating in several pathways of human cancer development.…”
Section: Discussionmentioning
confidence: 99%